2020
DOI: 10.1016/j.ejso.2020.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of neoadjuvant short-course radiotherapy and delayed surgery versus chemoradiation on postoperative outcomes in locally advanced rectal cancer patients – A propensity score matched nationwide audit-based study

Abstract: Objective: To investigate differences in postoperative outcomes between short-course radiotherapy and delayed surgery (SCRT-delay) and chemoradiation (CRT) in patients with locally advanced rectal cancer (LARC). Background: Previous trials suggest that SCRT-delay could serve as an adequate neoadjuvant treatment for LARC. Therefore, in frail LARC patients SCRT-delay is recommended as an alternative to CRT. However, data on postoperative outcomes after SCRT-delay in comparison to CRT is scarce. Methods: This was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…In the Stockholm III trial, the experimental arm showed an increasing pCR rate if surgery was delayed for four to eight weeks after SCRT, and it could reach 11.8%, compared to 2.1% in the SCRT with the immediate surgery group [11]. According to previous studies, an increasing pathological response was observed after SCRT with delayed surgery; however, the pCR rate was not greater than after conventional CRT [13,[20][21][22][23]. Moreover, the pooled results in this meta-analysis showed a significantly lower pCR rate compared to conventional CRT in patients who underwent SCRT followed by delayed surgery without consolidation chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Stockholm III trial, the experimental arm showed an increasing pCR rate if surgery was delayed for four to eight weeks after SCRT, and it could reach 11.8%, compared to 2.1% in the SCRT with the immediate surgery group [11]. According to previous studies, an increasing pathological response was observed after SCRT with delayed surgery; however, the pCR rate was not greater than after conventional CRT [13,[20][21][22][23]. Moreover, the pooled results in this meta-analysis showed a significantly lower pCR rate compared to conventional CRT in patients who underwent SCRT followed by delayed surgery without consolidation chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen studies enrolling 7507 rectal cancer patients from 13 cohorts were included in this meta-analysis [13][14][15][16][20][21][22][23][24][25][26][27][28][29][30][31][32]. Of these, two studies reported different parameters of the same cohort [28,29], four studies reported survival outcomes at different time points [13,14,20,24], and one study reported an expanded enrollment including the preliminary cohort [31].…”
Section: Characteristics Of the Included Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Elderly patients more often have a comorbidity, disability, geriatric diseases and consequently physical impairment, and they tend to undergo abdominal surgery less often because of the higher risk of perioperative complications [ 4 , 9 ]. In order to reduce these complications, multimodal therapy modifications are often used in elderly rectal cancer patients, such as reduction of chemotherapy dose or choosing short-course radiotherapy (RT) with delayed surgery [ 7 , 10 , 11 , 12 ]. Moreover, resection with colostomy formation without an anastomosis is often used to reduce postoperative risks of anastomotic leakage [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%